A genome-wide DNA methylation signature for SETD1B-related syndrome - I. M. Krzyzewska (18614968) (2019)
SETD1B is a component of a histone methyltransferase complex that specifically methylates Lys-4 of histone H3 (H3K4) and is responsible for the epigenetic control of chromatin structure and gene expression. De novo microdeletions encompassing this gene as well as de novo missense mutations were previously linked to syndromic intellectual disability (ID). Here, we identify a specific hypermethylation signature associated with loss of function mutations in theSETD1Bgene which may be used as an epigenetic marker supporting the diagnosis of syndromicSETD1B-related diseases. We demonstrate the clinical utility of this unique epi-signature by reclassifying previously identifiedSETD1BVUS (variant of uncertain significance) in two patients. Other Information Published in: Clinical Epigenetics License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1186/s13148-019-0749-3